Analisis Strategi dan Metode Pembelajaran Bahasa Arab di Asrama Bahasa Arab Manhalun Nabighin - Mandalika Mandalika (Yayasan Haiah Nusratul Islam, 2023)
Arabic is one of the languages that is often considered difficult by every individual, in Indonesia Arabic is rarely used in everyday language and there are several problems that occur both linguistically and non-linguistically, namely in linguistics including morphology and syntax. While in non-linguistics including the learning environment, learning motivation and also learning time. These problems can be overcome by the existence of Arabic language learning in religion-based schools, several ma'had and also language courses that are already widespread in Indonesia. this research uses qualitative or observational methods. this method is a research method that describes correctly formed with words based on relevant data collection and analysis techniques from natural situations. The results of the study show that the Manhalun Nabighin Arabic language dormitory is a representation for those who want to learn and explore Arabic, but one of the shortcomings that researchers get is that the learning time period is still very lacking for those who are categorized as beginners.